Validity of Interactive Learning Media Using Sparkol Videoscribe on Limits of Algebra Functions for Class XI IPS 1 SMAN 12 Padang - Miranty Novita Sari; Sefna Rismen; Lita Lovia (Department of Mathematics, Universitas Negeri Padang (UNP), 2022)
The development of IT in the 21st century has become the main complement in every learning activity such as using learning media. Learning media is a tool that can help the learning process so that learning objectives are conveyed. This study aims to produce interactive learning media using Sparkol Videoscribe on valid algebraic function limits. This research is a Research and Development (R&D) research with a four-D (4-D) development model. The subjects in this study were students of class XI IPS 1 SMAN 12 Padang. The data collection technique used a validation sheet. The results of this study are: Validity of interactive learning media using Sparkol Videoscribe which is designed to be very valid with the percentage results obtained 95.99% with a very valid category. Based on the results of the study, it can be concluded that the validity of interactive learning media using Sparkol Videoscribe is valid and feasible to use on the material limit of algebraic functions for class XI IPS 1 SMAN 12 Padang.